Who makes partner in Big 4 audit firms? – Evidence from Germany - Downar, Benedikt; Ernstberger, Jürgen; Koch, Christopher (Accounting, Organizations and Society, 2021)
This study investigates who makes partner in Big 4 audit firms. Building on prior qualitative research, we conduct the first large scale study using archival data to examine the incremental importance of different individual auditor characteristics for making partner. For our analyses, we collect information on German auditors from a business-oriented social network site. We conduct a longitudinal analysis for a cohort of Big 4 senior managers and directors to identify determinants of making partner. We find that economic capital, social capital, and institutionalized cultural capital matter for making partner. Further, we find that female and foreign auditors are less likely to become partner than their counterparts. In addition, we perform a cross-sectional analysis using a larger sample of auditors to identify the distinct characteristics of Big 4 partners compared to Big 4 senior managers, Big 4 directors, and non-Big 4 partners, and find results consistent with the longitudinal analysis.